2010
DOI: 10.1586/eri.10.125
|View full text |Cite
|
Sign up to set email alerts
|

The use of a neonatal mouse model to study respiratory syncytial virus infections

Abstract: Respiratory syncytial virus (RSV) infection is the most significant cause of viral death in infants worldwide. The significant morbidity and mortality associated with this disease underscores the urgent need for the development of an RSV vaccine. The development of an RSV vaccine has been hampered by our limited understanding of the human host immune system, which plays a significant role in RSV pathogenesis, susceptibility and vaccine efficacy. As a result, animal models have been developed to better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 91 publications
4
73
0
Order By: Relevance
“…Likewise, specific mouse strains, including New Zealand Black mice (which have inherent impaired macrophage function) (96), and gene-targeted mice deficient for Toll-like receptor (TLR)2, TLR4, TLR6 and TLR7 (65,68,81) show increased susceptibility for hRSV. Unlike in humans, young age in mice is not an important risk factor for severe primary LRTD (51) although age at initial infection as been reported to play a critical role in the development of delayed sequelae of pulmonary dysfunction, with younger mice experiencing increased airway hyperreactivity with enhanced mucus production, eosinophilic inflammation, and Th2 responses upon reinfection during later life (27,29,31).…”
Section: Heterologous (Nonhuman) Hrsv Modelsmentioning
confidence: 99%
“…Likewise, specific mouse strains, including New Zealand Black mice (which have inherent impaired macrophage function) (96), and gene-targeted mice deficient for Toll-like receptor (TLR)2, TLR4, TLR6 and TLR7 (65,68,81) show increased susceptibility for hRSV. Unlike in humans, young age in mice is not an important risk factor for severe primary LRTD (51) although age at initial infection as been reported to play a critical role in the development of delayed sequelae of pulmonary dysfunction, with younger mice experiencing increased airway hyperreactivity with enhanced mucus production, eosinophilic inflammation, and Th2 responses upon reinfection during later life (27,29,31).…”
Section: Heterologous (Nonhuman) Hrsv Modelsmentioning
confidence: 99%
“…Our and other laboratories have therefore developed a neonatal mouse model that better mimics RSV disease in infants (4)(5)(6)(7)(8)(9). In this model, neonatal mice (Ͻ7 days old) are infected with RSV and various immunological parameters are measured.…”
mentioning
confidence: 99%
“…The neonatal mouse model of RSV infection has proven to be an invaluable model to study and understand RSV pathogenesis in infants (5). Using this model, we have recently demonstrated that interleukin 4 receptor ␣ (IL-4R␣) on Th cells plays a pathogenic role in RSV reinfection-associated immunopathophysiology (4).…”
mentioning
confidence: 99%
“…Histopathological lesions include perivasculitis and peribronchiolitis, and in some cases, interstitial pneumonia is observed [67,68]. In terms of age, experimentally infected neonatal Balb/c mice develop asthma-like symptoms such as airway hyperreactivity, mucus overproduction, eosinophilia and a distinct Th2-biased response [51, 67,73]. In contrast, RSV infection in adult Balb/c mice induces a Th1-biased response, with high concentrations of IFN-γ in both lung and BALF [68,73].…”
Section: Cotton Ratmentioning
confidence: 99%
“…In terms of age, experimentally infected neonatal Balb/c mice develop asthma-like symptoms such as airway hyperreactivity, mucus overproduction, eosinophilia and a distinct Th2-biased response [51, 67,73]. In contrast, RSV infection in adult Balb/c mice induces a Th1-biased response, with high concentrations of IFN-γ in both lung and BALF [68,73]. A clear downside of using this animal model is the numerous differences between innate and adaptive immune responses of humans and mice [67].…”
Section: Cotton Ratmentioning
confidence: 99%